How Scaffolding within Genre-Based Pedagogy Supports Students’ Transition to Independent Narrative Writing - Mery Ardiyani; Yousef Bani Ahmad; Wahyudin Fitriyana (Universitas Islam Negeri Palopo, 2026)
Writing is a complex skill for EFL students, requiring the integration of linguistic knowledge, organization, and meaning-making. This study aims to explore how scaffolding within Genre-Based Pedagogy (GBP) supports students’ transition to independent narrative writing. A qualitative case study design was employed involving secondary school EFL students. Data were collected through classroom observation and semi-structured interviews and analyzed using thematic analysis. The findings reveal that scaffolding embedded in the stages of GBP functions as an integrated system that gradually supports students’ learning. Through structured instruction, explicit modelling, and collaborative activities, students develop a clearer understanding of narrative structure and language features. Scaffolding also facilitates idea generation and organization while reducing common writing difficulties, such as limited vocabulary and coherence. As students progress through the stages, they demonstrate increased confidence and independence in constructing their own texts. The study concludes that scaffolding within GBP not only enhances students’ writing ability but also fosters learner autonomy. These findings highlight the importance of structured and systematic scaffolding in supporting effective writing instruction in EFL contexts.